Comparative study of legal terms in English and Uzbek languages with reference to international law and legal globalisation - Pulatova, Ugilkhon; Pulatova, Nodirakhon; Umarova, Iroda; Rasbergenova, Sarbinaz; Allashova, Shiyrinay (Comparative Legilinguistics, 2025)
This study presents a comparative analysis of English and Uzbek legal terminology within the framework of legal globalisation. Using a comparative method, it examines key terms drawn from international treaties and national legislation (e.g., “refugee”, “due diligence”, “jurisdiction”, “arbitration”), focusing on their adaptation and use in practice. The analysis highlights systemic differences: English terminology, shaped by common law and enriched with Latin borrowings, is concise and context-dependent, while Uzbek terminology, rooted in continental law, often relies on descriptive constructions and statutory rigidity. Three categories of terminological relationships are identified: direct equivalents (“arbitration” (арбитраж)), partial equivalents requiring cultural adaptation (“due diligence” (тегишли текширув)), and non-equivalent terms requiring explanatory translation (habeas corpus). Findings reveal that English increasingly influences Uzbek legal practice, but borrowing without contextualisation can lead to semantic distortion. The study also underscores the role of international organisations (e.g., UN, ICC) in promoting terminological standardisation. By documenting patterns of equivalence and divergence, this research provides both theoretical insights and practical implications for legal translators, comparative lawyers, and policymakers. It demonstrates that effective legal translation requires not only linguistic competence but also an understanding of distinct legal traditions and institutional frameworks.